(untitled) (Journal of European Studies (JES), 2021)
Religious extremism and terrorism in the name of Islam have been contentious issues in Europe and the West for well over a decade. Far-right extremism, however, is an emerging spectre that haunts Europe today. While there are indeed concerns about right-wing terrorism in Europe that are growing owing to a series of recent attacks by right-wing terrorists, far-right extremism is still low on the security agenda in Europe. This is despite the transnational nature of the far-right movement which makes it potentially dangerous for Europe and the West. This paper discusses challenges and complexities in countering far-right extremism, such as Western media bias, the definition of right-wing terrorism and violence, and laws related to far-right extremism. It has suggested to the European policymakers to revisit their security narrative for countering far-right extremism.